2023
DOI: 10.14232/jengeo-2023-44670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molasses Application on Soil Biological Indicators and Maize Growth of Different Tillage Soil

Priyo Adi Nugroho,
Nándor Prettl,
Zsolt Kotroczó
et al.

Abstract: Soil enzyme activity and labile carbon (LC) have long been used as soil health indicators. Soil health can be improved by molasses addition resulting in better plant growth and productivity. The effect of molasses on soil biological activity and plant growth under different tillage soil has not been discussed in many studies in Hungary. We assessed two soil types under different long-term tillage practices: conservation tillage (CT), which leaves 30% or more residue on the soil surface, and conventional-plough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Studies have shown that the use of molasses and its mixtures with organic and mineral fertilizers improves soil fertility and increases the yield of spinach, sugar beet, corn, lettuce, and other plants [26][27][28][29][30]. Molasses mixtures increase the amount of carbon, nitrogen, and potassium in the soil and its availability to plants, thus improving the conditions of plant germination and growth and the quality indicators of the harvested crop [27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the use of molasses and its mixtures with organic and mineral fertilizers improves soil fertility and increases the yield of spinach, sugar beet, corn, lettuce, and other plants [26][27][28][29][30]. Molasses mixtures increase the amount of carbon, nitrogen, and potassium in the soil and its availability to plants, thus improving the conditions of plant germination and growth and the quality indicators of the harvested crop [27,30,31].…”
Section: Introductionmentioning
confidence: 99%